Calculation of calibration factors from the comparative fishing trial between FRS Africana and RV Dr Fridtjof Nansen - Antony, Luyanda Lennox (Department of Statistical Sciences, 2014)
Includes abstract. Includes bibliographical references (leaves 153-157).